400 TW operation of Orion at ultra-high contrast. (15th August 2018) - Parker, Stefan; Danson, Colin; Egan, David; Elsmere, Stephen; Girling, Mark; Harvey, Ewan; Hillier, David; Hussey, Dianne; Masoero, Stephen; McLoughlin, James; Penman, Rory; Treadwell, Paul; et al.
Abstract : The Orion facility at the Atomic Weapons Establishment in the United Kingdom has the capability to operate one of its two 500 J, 500 fs short-pulse petawatt beams at the second harmonic, the principal reason being to increase the temporal contrast of the pulse on target. This is achieved post-compression, using 3 mm thick type-1 potassium dihydrogen phosphate crystals. Since the beam diameter of the compressed pulse is ${\sim}600$ mm, it is impractical to achieve this over the full aperture due to the unavailability of the large aperture crystals. Frequency doubling was originally achieved on Orion using a circular sub-aperture of 300 mm diameter. The reduction in aperture limited the output energy to 100 J. The second-harmonic capability has been upgraded by taking two square 300 mm $×$ 300 mm sub-apertures from the beam and combining them at focus using a single paraboloidal mirror, thus creating a 200 J, 500 fs, i.e., 400 TW facility at the second harmonic.